(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
Fluorspar mining poses significant environmental and health risks, including toxicity, as it contaminates nearby water bodies, which can lead to fluorosis, characterized by brown teeth and skeletal deformities among residents. This study analyzed two fluorspar mineral samples—Greenish brown (A) and Bluish brown (B)—collected from Liji Hills, near Gombe, to determine their metal oxide composition, crystal structure, and physicochemical properties, and to compare these values with the WHO permissible limits. Physicochemical analysis revealed that the pH of sample A decreased with time (mean = 6.91), while sample B fluctuated (mean = 6.71). Electrical conductivity decreased with time for both samples, averaging 0.25 N S cm⁻¹ for A and 0.29 N S cm⁻¹ for B. Ash content was 3.7 % for A and 2.9 % for B, while moisture content was 4.16 % and 1.0 %, respectively. X-ray fluorescence (XRF) analysis of sample A indicated major oxides in descending order: CaO = 91.5 mg L⁻¹ > SiO₂ = 3.36 mg L⁻¹ > Al₂O₃ = 0.818 mg L⁻¹ > P₂O₅ = 0.593 mg L⁻¹ > TiO₂ = 0.463 mg L⁻¹ > Fe₂O₃ = 0.418 mg L⁻¹ > MnO = 0.0246 mg L⁻¹ > K₂O = 0.0051 mg L⁻¹. Sample B showed CaO = 81.4 mg L⁻¹ > Fe₂O₃ = 6.63 mg L⁻¹ > SiO₂ = 5.65 mg L⁻¹ > TiO₂ = 0.879 mg L⁻¹ > P₂O₅ = 0.612 mg L⁻¹ > MnO = 0.0204 mg L⁻¹. X-ray diffraction (XRD) revealed that sample A had an average crystallite size of 75.87 nm with a face-centered cubic structure and Bragg angles between 25.75° and 68.77°, while sample B had a size of 13.65 nm with similar symmetry and Bragg angles from 25.94° to 56.17°. Both samples exceeded WHO limits for CaO and Fe₂O₃, indicating contamination risk. Although Pb and As were not detected, the greenish-brown sample exhibited a higher metal oxide content and greater structural quality, suggesting that Liji Hills fluorspar may contribute to environmental pollution and adverse health outcomes in nearby communities.